The Competitiveness of Global Port-Cities: The Case of Mersin, Turkey - Merk, Olaf (OECD Regional Development Working Papers, 2013)
This working paper offers an evaluation of the performance of the port of Mersin, an analysis of the impact of the port on its territory and an assessment of policies and governance in this field. It examines port performance over the last decades and identifies the principal factors that have contributed to it. The effect of the ports on economic and environmental questions is studied and quantified where possible. The value added of the port cluster of Mersin is calculated and its interlinkages with other economic sectors in Turkey delineated. The major policies governing the ports are assessed, along with policies governing transport and economic development, the environment and spatial planning. These include measures instituted by the port authorities, as well as by local, regional and national governments. Governance mechanisms at these different levels are described and analysed. Based on the report's findings, recommendations are proposed with a view to improving port performance and increasing the positive effects of the port of Mersin on its territory